Relationship of Obesity with Lifestyle and Comorbidities in Public School Teachers—A Cross-Sectional Study - Tebar, William R.; Gil, Fernanda C. S. [UNESP]; Delfino, Leandro D. [UNESP]; Souza, Jefferson M. [UNESP]; Mota, Jorge; Christofaro, Diego G. D. [UNESP] (MDPI, 2022)
Obesity is one of the major public health burdens, and is a global pandemic that has been associated with lifestyle habits and comorbidities in the general population. Teachers comprise a wide category of workers with unestablished factors associated with obesity. This cross-sectional epidemiological study analyzed the association of obesity, defined by body mass index ≥ 30 kg/m², with work-related factors (years in the profession, hours worked weekly), lifestyle (sports practice, active commuting, TV viewing, smoking, alcohol consumption), and comorbidities (hypertension, diabetes, dyslipidemia) in a sample of 246 public school teachers. An elevated prevalence of obesity was observed in the sample (30.1%), which was associated with ≥2 h/day of TV viewing (OR: 2.10, p = 0.025) and hypertension (OR: 2.62, p = 0.010), whereas it was inversely associated with frequent active commuting by walking or cycling (OR: 0.22, p = 0.007), even after multiple adjustments. No association was observed between obesity and work-related factors. Actions focused on promoting active commuting while limiting TV time could be important strategies for facing the elevated prevalence of obesity in public school teachers. However, the analysis of longitudinal data and investigation of obesogenic determinants are still needed.
Keywords: active commuting; body mass index; chronic diseases; physical activity; screen time